2007
DOI: 10.1002/cvde.200606574
|View full text |Cite
|
Sign up to set email alerts
|

CVD of MgO Thin Films from Bis(methylcyclopentadienyl) Magnesium

Abstract: Thin films of MgO are grown by CVD, with a high growth rate, on Si(001) and quartz substrates in the temperature range 400-550°C, using bis(methylcyclopentadienyl)magnesium [Mg(CH 3 -C 5 H 4 ) 2 ] as the precursor. The films obtained are investigated by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and optical absorption, in order to investigate the interrelations between film properties and processing conditions. Cubic phase MgO (periclase) films, characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…For the O 1 s spectrum (Fig. 1 f), three peaks at 530.1, 531.7, and 533.3 eV could be assigned to the O–Mg, O–C, and O=C bonds, respectively [ 28 , 29 ]. It is worth noting that the peak at ~533.3 eV should not be assigned to the peroxide magnesium species because the products were conducted through the annealing process at 750 °C [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the O 1 s spectrum (Fig. 1 f), three peaks at 530.1, 531.7, and 533.3 eV could be assigned to the O–Mg, O–C, and O=C bonds, respectively [ 28 , 29 ]. It is worth noting that the peak at ~533.3 eV should not be assigned to the peroxide magnesium species because the products were conducted through the annealing process at 750 °C [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] Moreover, MgO thin lms can be used for the protection of plasma display panels from erosion by ion bombardment. 17 Several deposition methodologies for MgO and ZnO layer formation exist, including the sol-gel process in combination with spin-coating, 18,19 spray pyrolysis, 20,21 pulsed laser deposition, 22,23 molecular beam epitaxy, 24 as well as metal-organic gas phase deposition techniques such as CVD (¼ chemical vapor deposition) [25][26][27] and ALD (¼ atomic layer deposition). 28,29 Among them, CVD and spin-coating provide convincing alternatives owing to their simplicity of processing control, covering of large areas and their capability to allow adherent and reproduceable lms at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ZnEt 2 shows undesired pre-reactions and hence decomposition by the deposition of particulates, upstream from the heating element may occur during the precursor delivery. 32,39,43 For MgO lm formation, bis(cyclopentadienyl) magnesium, 25,44 alkylmagnesium alkoxides, 45,46 magnesium carboxylates, 47,48 magnesium b-ketoiminates, 49 magnesium bdiketonates 26 and their diamine adducts 12,50,51 are usually used as CVD precursors of which the latter ones are promising CVD candidates, due to their high volatility, good stability in the condensed and gas phase, and their straightforward synthetic procedure. 12,50,51 In contrast, as spin-coating precursors mainly magnesium acetate tetrahydrate or zinc acetate dihydrate were used for the formation of the respective metal oxide layers.…”
Section: Introductionmentioning
confidence: 99%
“…9 The conduction and valence band offsets between MgO and silicon are determined to be 4.1 and 1.5 eV, which provide high enough energy barriers for electrons and holes in a Si substrate. 10 An MgO thin film has been grown by various deposition techniques, such as chemical vapor deposition, 11 atomic layer deposition ͑ALD͒, 12,13 and sol-gel processes. 14 It has also been reported that MgO thin films deposited by sputtering a magnesium target on Si have sharp interfaces with interface trap densities at the MgO/Si interface comparable to the conventional SiO 2 /Si system.…”
mentioning
confidence: 99%